La indebida aplicación de los deudores subsidiarios de las pensiones alimenticias por deuda o indisposición económica de los obligados principales, en los juzgados de la niñez y adolescencia de la ciudad de Machala en el año 2011. - Guzmán Lozada, Jorge Eduardo (2013)
The unnumbered Article 5 of the Code of childhood and adolescence, you have to see to food states that in the case of absence, incapacity, insufficient resources defendant, payment of alimony shall be assumed by family in this order, grandparents, brothers and uncles over 21 years. Leaving loopholes for fair pay for sinners, allowing the grandparents of the child for whom alimony is claimed go to prison, even when these are not paid when they are older. This research is aimed to ensure that the rights of persons seniors can not violate or scarce resource with a misapplication of the subsidiary debtors to provide rights of food to children without a study is conducted socioeconomic prior to that their rights are not violated, and continue to give these legal social problems.